UJI ULTRADRY VACUUM UNTUK MENINGKATKAN VIABILITAS PENYIMPANAN BENIH MALAPARI (Pongamia pinnata Merril.) - Asri Insiana Putri; Jayusman Jayusman (Jurnal Pemuliaan Tanaman Hutan, 2015)
Malapari (Pongamia pinnata) seeds have low sensitivity to desiccation and freezing storage. In the effort to improve the viability of seed storage, preliminary test of the vacuum ultradry storage techniques were important to be done. The purpose of this study was to attain lengthen periode of viability seeds with vacuum ultradry technics. All parameters of the treatment with a vacuum ultradry technique showed better results than the control. Interaction between humidity and incubation period have significantly influnces on shoots length. Interaction between moisture with incubation period and intercation beetwen humidity with temperatures has significant effect on root length. Interaction between moisture, incubation period and temperature have significantly affect to vigor index. The highest vigor index was 8.1050 at 20% humidity, 12 weeks incubation period with temperature 5C,86% higher than in the control.